A Viral Vectored Prime-Boost Immunization Regime Targeting the Malaria Pfs25 Antigen Induces Transmission-Blocking Activity - Goodman, Anna L. (Public Library of Science, 2011)
The ookinete surface protein Pfs25 is a macrogamete-to-ookinete/ookinete stage antigen of Plasmodium falciparum, capable of exerting high-level anti-malarial transmission-blocking activity following immunization with recombinant protein-in-adjuvant formulations. Here, this antigen was expressed in recombinant chimpanzee adenovirus 63 (ChAd63), human adenovirus serotype 5 (AdHu5) and modified vaccinia virus Ankara (MVA) viral vectored vaccines. Two immunizations were administered to mice in a heterologous prime-boost regime. Immunization of mice with AdHu5 Pfs25 at week 0 and MVA Pfs25 at week 10 (Ad-MVA Pfs25) resulted in high anti-Pfs25 IgG titers, consisting of predominantly isotypes IgG1 and IgG2a. A single priming immunization with ChAd63 Pfs25 was as effective as AdHu5 Pfs25 with respect to ELISA titers at 8 weeks post-immunization. Sera from Ad-MVA Pfs25 immunized mice inhibited the transmission of P. falciparum to the mosquito both ex vivo and in vivo. In a standard membrane-feeding assay using NF54 strain P. falciparum, oocyst intensity in Anopheles stephensi mosquitoes was significantly reduced in an IgG concentration-dependent manner when compared to control feeds (96% reduction of intensity, 78% reduction in prevalence at a 1 in 5 dilution of sera). In addition, an in vivo transmission-blocking effect was also demonstrated by direct feeding of immunized mice infected with Pfs25DR3, a chimeric P. berghei line expressing Pfs25 in place of endogenous Pbs25. In this assay the density of Pfs25DR3 oocysts was significantly reduced when mosquitoes were fed on vaccinated as compared to control mice (67% reduction of intensity, 28% reduction in prevalence) and specific IgG titer correlated with efficacy. These data confirm the utility of the adenovirus-MVA vaccine platform for the induction of antibodies with transmission-blocking activity, and support the continued development of this alternative approach to transmission-blocking malaria subunit vaccines.